2002
DOI: 10.1159/000063054
|View full text |Cite
|
Sign up to set email alerts
|

The effect of multiple simple Robertsonian heterozygosity on chromosome pairing and fertility of wild-stock house mice <i>(Mus musculus domesticus)</i>

Abstract: The influence of Robertsonian (Rb) heterozygosity on fertility has been the subject of much study in the house mouse. However, these studies have been largely directed at single simple heterozygotes (heterozygous for a single Rb metacentric) or complex heterozygotes (heterozygous for several to many metacentrics which share common chromosome arms). In this paper we describe studies on male multiple simple heterozygotes, specifically the F1 products of crosses between wild-stock mice homozygous for f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
69
0
5

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 34 publications
(50 reference statements)
8
69
0
5
Order By: Relevance
“…It has been demonstrated that house mice heterozygous for metacentrics have impaired reproductive fitness (for example, Wallace et al, 1992Wallace et al, , 2002SaĂŻd et al, 1993;Hauffe and Searle, 1998), and that there are recombination effects in the vicinity of the centromere in such heterozygotes (for example, Davisson and Akeson, 1993;Bidau et al, 2001;Merico et al, 2003). Thus, one or both of these processes could affect gene flow in the centromeric region of the metacentric chromosomes investigated by us.…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 99%
“…It has been demonstrated that house mice heterozygous for metacentrics have impaired reproductive fitness (for example, Wallace et al, 1992Wallace et al, , 2002SaĂŻd et al, 1993;Hauffe and Searle, 1998), and that there are recombination effects in the vicinity of the centromere in such heterozygotes (for example, Davisson and Akeson, 1993;Bidau et al, 2001;Merico et al, 2003). Thus, one or both of these processes could affect gene flow in the centromeric region of the metacentric chromosomes investigated by us.…”
Section: Relationship Of Madeiran Metacentric Mice With Those Of Elsementioning
confidence: 99%
“…The fact that one of the chromosomes homologous to the Y chromosome is fused to two different chromosomes in this species pair may have interesting evolutionary implications (Figure 5b). This is likely to result in a significant level of infertility in potential F 1 hybrids because of abnormal meiotic segregation (Wallace et al, 2002). This effect would likely be compounded if the chromosome happened to harbor sex-determining genes, given the disproportionate importance of sex chromosomes in the evolution of post-mating isolation mechanisms (Presgraves, 2008;Kitano et al, 2009).…”
Section: E Virescens Species Pairmentioning
confidence: 99%
“…Heterozygous disadvantage for chromosomal rearrangements results from the incorrect segregation of chromosomes during meiosis, leading to the formation of fertile aneuploid gametes and embryonic mortality (King, 1993;Marchetti et al, 1999). Premeiotic perturbations have been also observed in some cases causing a reduction in germ cell number (Garagna et al, 1990;Hauffe and Searle, 1998;Banaszek et al, 2000;Wallace et al, 2002). Data from different mammalian species (including human) have shown that values of underdominance vary according to the nature of the rearrangement, the chromosomes concerned, the breakpoint site, the gender and also the genetic context and age (King, 1993;Searle, 1993;Djelati et al, 1997;Hauffe and Searle, 1998;Castiglia and Capanna, 2000;Wallace et al, 2002;Pellestor et al, 2005;Anton et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Heterozygotes for fusions produce trivalents at meiosis, formed by the pairing of each metacentric and its two acrocentric homologs. These meiotic configurations usually result in very low nondisjunction (NDJ) rates when few in number, but the degree of gametogenetic impairment increases when many are present (Garagna et al, 1990;Hauffe and Searle, 1998;Castiglia and Capanna, 2000;Wallace et al, 2002). In some instances, however, parapatric Rb races carry monobrachially homologous fusions; that is, Rb metacentrics that have one chromosome arm in common.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation